Metastatic Renal Cell Cancer to Thyroid Diagnosed by Endoscopic Ultrasound Guided Fine Needle Aspiration Technique - Yousef Abdel-Aziz; Tariq Hammad; Mohamad Nawras; Hayder Abdulwahid; Ali Nawras (Case Reports in Gastrointestinal Medicine)
Medical literature about the role of endoscopic ultrasound (EUS) in identifying thyroid lesions is limited. We present a case of secondary thyroid cancer from renal cell carcinoma (RCC) metastasis, diagnosed by thyroid EUS-fine needle aspiration (FNA) approach that was done for staging of esophageal adenocarcinoma, in a patient with 11-year history of complete right nephrectomy for RCC. An 81-year-old female patient underwent EUS for the evaluation of a newly discovered distal esophageal cancer. A hypoechoic, round, and well-demarcated mass that measured 26.9 mm × 21.9 mm was noticed in the right lobe thyroid gland. Therefore FNA was performed. The cytological results were consistent with metastatic RCC. In conclusion, EUS-FNA of thyroid nodule is a feasible and safe technique that can be used to evaluate any suspicious thyroid nodule. This case emphasizes the importance of carefully examining the thyroid gland during routine upper esophageal EUS examinations in the presence of history of nonthyroidal cancer.